Reservoir engineering studies of small low-temperature hydrothermal systems in Iceland - Axelsson, Gudni (National Energy Authority, Grensasvegur, Reykjavik, IS, 1991)
Geothermal energy provides more than one third of the energy consumed in Iceland. Its primary use is for space heating and most of the 28 public hitaveitur (district heating services) in Iceland utilize small low-temperature geothermal fields that have a natural heat output of only a few 100 kWsub t to a few MWsub t. All of these small reservoirs respond to production by declining pressure and some by declining temperature. During the 1980's the emphasis in geothermal research in Iceland shifted from exploration to reservoir engineering. The reservoir engineering work carried out concurrent with the exploitation of these small fields includes: testing of individual wells, field wide tests, monitoring the response of reservoirs to long-term production and simple modeling.